Monetary policy before and after the euro: Evidence from Greece - Michael G. Arghyrou (Cardiff University, Cardiff Business School, 2006)
We model Greek monetary policy in the 1990s and use our findings to address two interrelated questions. First, how was monetary policy conducted in the 1990s so that the hitherto highest-inflation EU country managed to join the euro by 2001? Second, how compatible is the current ECB monetary policy with Greek economic conditions? We find that Greek monetary policy in the 1990s was: (i) primarily determined by foreign (German/ECB) interest rates though still influenced, to some degree, by domestic fundamentals; (ii) involving non-linear output gap effects; (iii) subject to a deficit of credibility culminating in the 1998 devaluation. On the question of compatibility our findings depend on the value assumed for the equilibrium post-euro real interest rate and overall indicate both a reduction in the pre-euro risk premium and some degree of monetary policy incompatibility. Our analysis has policy implications for the new EU members and motivates further research on fast-growing EMU economies.
Keywords: C51; C52; E43; E58; F37; 330; monetary policy; reaction function; non-linear; compatibility; Greece; EMU; Geldpolitik; Mitgliedschaft; Europäische Wirtschafts- und Währungsunion; Zinsstruktur; Wirtschaftliche Anpassung; Modellierung; Schätzung; Griechenland